On verb second and the så-construction in two Mainland Scandinavian contact situations - Sollid, Hilde; Eide, Kristin M. (Nordlyd, 2008)
Data from areas of long term language contact situations between a non-V2 language and a V2 language in Northern Norway reveal unstable use of V2. Furthermore, in a substantial portion of the data there is a notable presence of the particle så. These facts are discussed in light of data on the så-construction in Standard Norwegian and Finland Swedish, and the particle ni in Finnish. We suggest that some aspects of så in the data may be explained as one trait of L1 transfer, where the acquirer recruits existing L2 elements and assigns to them new tasks in the grammar. The data reveal interesting variation patterns, which may be taken to support the “Underspecified CP” hypothesis put forth in recent language acquisition research.
Keywords: language contact; non-V2; transfer; Mainland Scandinavian; Finnish; så-construction